Salient Predictors of Behavioural Intention to Use PictureThis Artificial Intelligence Technology for Plant Identification by Undergraduate Students in Public Universities in Uganda - Bukenya, John; Muyinda, Paul Birevu; Isabwe, Ghislain Maurice Norbert; Mayende, Godfrey; Kalema, James (American Journal of Education and Practice, 2025)
Purpose: The purpose of the study was to examine the influence of behavioural intention (BI) predictors on the intention to use artificial intelligence (AI) technology, Picture This, for plant identification by undergraduate students in public universities in Uganda. Materials and Method: The study was carried out using a correlational, cross-sectional survey method based on a research instrument developed from the extended unified theory of acceptance and use of technology (UTAUT2). Findings: The findings of the study show that five BI predictors namely, performance expectancy (β = 0.278, p = 0.000 < 0.05), effort expectancy (β = 0.118, p = 0.006 < 0.05), social influence (β = 0.104, p = 0.009 < 0.05), hedonic motivation (β = 0.292, p = 0.000 < 0.05) and habit (β = 0.106, p = 0.011 < 0.05) positively and significantly influence intention to use Picture, This AI by undergraduate students in Uganda’s public universities. Unique Contribution to Theory, Practice and Policy: The study was informed by UTAUT2 which posits that use behaviour of technology is influenced by behavioural intention, coupled with habit and facilitating conditions. To the university management, we suggest that appropriate facilities should be put in their institutions to enhance AI’s contribution to performance expectancy, effort expectancy, hedonic motivation, social influence and price value in order to improve students’ behavioural intention and ultimately use behaviour of AI technology for better learning experiences and improved learning outcomes. To the student community pursuing biological and agricultural sciences, we recommend the adoption of Picture. This AI as a learning tool for use during plant identification.